Effectiveness of tadalafil and tamsulosin combination in benign prostatic hyperplasia: A prospective cohort study at a tertiary care center - Sudarsan S; Prabhu T; Rajsri TR; Laishram Sanjana (Asian Journal of Medical Sciences, 2023)
Background: Benign prostatic hyperplasia (BPH) is one of the major causes of lower urinary tract symptoms (LUTS) in men. The uroselective tamsulosin helps in rapid reduction of prostate symptoms and its combination with Tadalafil, a phosphodiesterase inhibitor leads to synergistic benefit improving the LUTS of BPH. Aims and Objectives: This study was conducted with the aim to assess the effectiveness of synergistic effect of Tadalafil and Tamsulosin in improving the symptoms of BPH patients. Materials and Methods: A prospective cohort study was conducted among the patients admitted with LUTS due to BPH in the surgery ward of Annapoorna Medical College. A total of 100 patients were included in the study. The control group was administered 0.4 mg of tamsulosin and the study group was administered with combination of tadalafil 5 mg and tamsulosin 0.4 mg for 3 weeks and followed up at an interval of 3 weeks, 1 month, and 6 months. Paired t-test was used to compare the international prostate symptom score (IPSS) mean scores. Results: A total of 100 patients were included in the study. There was significant improvement in the post-voided volume of the study group in comparison to the control. The IPPS score of the study group at the baseline was 16.39±4.89 which was decreased to a score of 11.42±3.39 after the combination drug therapy with P<0.001 which was statistically significant. Conclusion: The combination therapy of tamsulosin and tadalafil marked an improvement in the symptoms of BPH which can be noted with fall down of IPSS score after the therapy.